Desain Interior Masjid Al-Muttaqin: Meningkatkan Ruang Ibadah Dan Sosial Melalui Pendekatan Kearifan Lokal - Imam Sumarwoto; Marselly Dwiputri; Rafi Mentari; Sarah Aisha (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This community service project produced a conceptual interior design for Al-Muttaqin Mosque, integrating Islamic spiritual values with local wisdom. The design process adopted a participatory approach, involving mosque administrators and congregants to identify spatial needs and cultural identity. The main concept, “Simplicity in Wisdom,” is expressed through the use of natural materials such as wood, stone, and exposed brick, creating a warm and honest atmosphere in harmony with nature. A small reflective pool in front of the mihrab serves as a calming psychological element, while natural lighting enhances spiritual ambience and ecological balance. The mosque’s terrace functions as a social space that fosters interaction among worshippers, reflecting the local values of cooperation and togetherness. Overall, this design represents not only visual aesthetics but also a dialogue between tradition and modernity within the context of contemporary Islamic architecture in Indonesia.